Structural integrity assessment and rehabilitating of Hercilio Luz bridge (Fracture and Structural Integrity, 2017)
The Hercílio Luz suspension bridge, built in 1926, has been out of service since 1991 due to high corrosion levels and structural element impairment. A complete rehabilitation project was developed which included the replacement of the impaired items and foundation strengthening. For this, an auxiliary structure was employed to support the central span during the rehabilitation process. A carefully studied load transfer process, where the central span loading is transferred from the eye-bar towards the auxiliary structure will be performed. For this purpose, a synchronized jacking sequence will be used, which was predefined by means of numerical model analysis. All structural elements had their designs evaluated and some geometric changes were implemented. This paper presents all the methodology developed in the rehabilitation project of Hercilio Luz bridge, as well as the development stages up to the present date.
Keywords: Structural impairment evaluation; Bridge rehabilitation; Load transfer; Synchronized jacking